BIOACCUMULATION OF HEAVY METALS FROM THE SECONDARY TREATED MUNICIPAL WASTEWATER BY Lemna gibba L. - Obek, Erdal (Parlar Scientific Publications (P S P), 2009)
Since aquatic plants are effective in removing heavy metals from polluted waters, they are generally accepted as heavy metal bioaccumulators. They may have different accumulation capabilities and exhibit dissimilar tolerances of heavy metals. Among them, Lemna gibba was examined as a bioaccumulating plant in this study. The aim was to determine its heavy metal accumulating capability in secondary treatment effluent. Lemna gibba was collected from a natural lake in Elazig, Turkey, and then adapted to the effluent in-situ. The experiments in the present study showed that Lemna gibba accumulated high levels of Cr, Cu, Zn, Pb, Cd and Ni in the first few days, but then some decreases in the accumulation levels were recorded, most probably due to its saturation level. It can be concluded that Lemna gibba (duckweed) shows promise for the removal of Cr, Cu, Zn, Pb, Cd and Ni from contaminated wastewaters, since it accumulates high concentrations of these elements.
Keywords: Bioaccumulation; Lemna gibba L.; heavy metal; secondary treated municipal wastewater